Enrichment of cocoa drink with fruit syrups for school feeding - T. B. Kolotiy; O. S. Sakharova (Новые технологии)
One of the causes of frequent alimentary-dependent diseases in school-age children is the insufficient intake of micronutrients. Consumer products, basic necessities and the most beloved children's products play a huge role in the nutrition of schoolchildren. Drinks of increased nutritional and biological value, obtained by introducing functional ingredients into the composition with the maximum preservation of their original nutritional value can be a great prospect in improving school feeding.  The aim of the research is to study the effect of fruit syrups on the biological and nutritional value of a cocoa drink. The objects of study are the most promising fruits of the foothill zone of the Republic of Adygea: blackberry, raspberry.  The article presents the results of the study on the use of fruit syrups obtained from blackberries and raspberries in the preparation of cocoa drinks recommended for school meals. It has been experimentally established that 5 g, 10 g, 15 g and 20 g dosages of fruit syrups influence organoleptic, physical and chemical indicators of the quality of cocoa drinks. The optimal dosage of fruit syrups in the preparation of a cocoa drink has been established.  Fruit syrups have high biological activity, which will enrich cocoa drinks and give them a functional focus.